Last hired, first fired? Black-white unemployment and the business cycle - Kenneth A. Couch; Robert W. Fairlie (Institute for the Study of Labor (IZA), 2008)
Past studies have tested the claim that blacks are the last hired during periods of economic growth and the first fired in recessions by examining the movement of relative unemployment rates over the business cycle. Any conclusion drawn from this type of analysis must be viewed as tentative because the cyclical movements in the underlying transitions into and out of unemployment are not examined. Using Current Population Survey data matched across adjacent months from 1989 to 2004, this paper provides the first detailed examination of labor market transitions for prime-age black and white men to test the last-hired, first-fired hypothesis. Considerable evidence is presented that blacks are the first fired as the business cycle weakens. However, no evidence is found that blacks are the last hired. Instead, blacks appear to be initially hired from the ranks of the unemployed early in the business cycle and later are drawn from non-participation. The narrowing of the racial unemployment gap near the peak of the business cycle is driven by a reduction in the rate of job loss for blacks rather than increases in hiring.
urn:nbn:de:101:1-20081014110
Keywords: J15; 330; Race; unemployment; business cycle; Arbeitslosigkeit; Rasse; Ethnische Diskriminierung; Konjunktur; USA